Implementation of a Low-Cost Vehicular Vlc System and Can Bus Interface - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2018)
Vehicular communication networks are one of the essential technologies needed to implement intelligent transportation systems in smart cities. In such networks, available/licensed technologies still need to develop robustness and resilience to support critical applications for safety and efficiency. One novel technology, complementary to radio-frequency, is visible light communications (VLC), which has the potential of taking advantage of light emitting diodes (LEDs) that are widely deployed in car lamps and traffic lights. Control area network bus (CAN Bus), the control network of all modern cars, can be read through the on-board diagnostics (OBD) port available inside the cabin. Data from sensors and actuators of the car can be robustly acquired from the bus and can be shared to allow the vehicular network cooperatively build knowledge of the kinetic data of each car through beaconing. In this work, a low-cost VLC system based on white LED technology, which is increasingly replacing halogen bulbs in cars headlamps, is implemented and validated in laboratory conditions at a distance up to 1.5 meters between the transmitter and receiver. Further, the implementation of a low-cost CAN Bus interface is shown. Its velocity data acquisition is validated by testing the system against a global positioning system (GPS) device. The proposed low-cost CAN Bus interface achieved high reproducibility of the GPS estimations and was validated with a 0.9979 Lin s concordance correlation coefficient. © 2018 IEEE.